2022
DOI: 10.15252/embr.202254685
|View full text |Cite
|
Sign up to set email alerts
|

Lactate induces metabolic and epigenetic reprogramming of pro‐inflammatory Th17 cells

Abstract: Increased lactate levels in the tissue microenvironment are a wellknown feature of chronic inflammation. However, the role of lactate in regulating T cell function remains controversial. Here, we demonstrate that extracellular lactate predominantly induces deregulation of the Th17-specific gene expression program by modulating the metabolic and epigenetic status of Th17 cells. Following lactate treatment, Th17 cells significantly reduced their IL-17A production and upregulated Foxp3 expression through ROSdrive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…K, A, and methionine (M) residues were also often identified upstream of the Kla sites, whereas K, A, and G residues were more commonly observed downstream of the Kla sites. 17,35,37,38 These results demonstrated that some motifs in N. oceanica are conserved with other organisms, including higher plant rice, T. gondii, and B. cinerea, which implies that proteinlactylated modification is evolutionally conserved.…”
Section: ■ Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…K, A, and methionine (M) residues were also often identified upstream of the Kla sites, whereas K, A, and G residues were more commonly observed downstream of the Kla sites. 17,35,37,38 These results demonstrated that some motifs in N. oceanica are conserved with other organisms, including higher plant rice, T. gondii, and B. cinerea, which implies that proteinlactylated modification is evolutionally conserved.…”
Section: ■ Discussionmentioning
confidence: 65%
“…Certain amino acid residues around the Kla were found to be significantly enriched when evaluating the motif sequences in an enrichment heat map (Figure C,D). K, A, and methionine (M) residues were also often identified upstream of the Kla sites, whereas K, A, and G residues were more commonly observed downstream of the Kla sites. ,,, These results demonstrated that some motifs in N. oceanica are conserved with other organisms, including higher plant rice, T. gondii, and B.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…17,39 In addition, lactate has been revealed to function as a negative feedback signal to control immune cell metabolism, preventing overactive inflammatory response. 22,40,41 In general, our study has explored a novel application of lactate as an antiinflammatory agent and provided a possible explanation for yogurt as a potential dietary intervention strategy for people with psoriasis.…”
Section: Discussionmentioning
confidence: 99%